2017
DOI: 10.1007/s00404-017-4502-x
|View full text |Cite
|
Sign up to set email alerts
|

Can adnexal torsion be predicted by measuring plasma heat shock protein 70 level? An experimental study

Abstract: A significant increase in plasma heat shock protein 70 level in the study group indicates that plasma heat shock protein 70 level could be used as a serum marker in the early detection of adnexal torsion. However, further clinical and experimental studies of a larger size are required.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4

Citation Types

0
4
0

Year Published

2018
2018
2024
2024

Publication Types

Select...
4

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(4 citation statements)
references
References 31 publications
0
4
0
Order By: Relevance
“…Normal adnexal torsion is rare during pregnancy. Çılgın H et al [6] indicated that plasma heat shock protein 70 level could be used as a serum marker in the early detection of adnexal torsion since its significant increase in the study group was 1.50-fold and 1.47fold respectively (P = 0.001) than that in the laparotomy and control groups, following 12 h of adnexal torsion. Ayachi A et al [7] reported two cases of adnexal torsion during the second trimester of pregnancy; presenting with appendix syndrome the one and acute left iliac fossa pain the other.…”
Section: Discussionmentioning
confidence: 97%
“…Normal adnexal torsion is rare during pregnancy. Çılgın H et al [6] indicated that plasma heat shock protein 70 level could be used as a serum marker in the early detection of adnexal torsion since its significant increase in the study group was 1.50-fold and 1.47fold respectively (P = 0.001) than that in the laparotomy and control groups, following 12 h of adnexal torsion. Ayachi A et al [7] reported two cases of adnexal torsion during the second trimester of pregnancy; presenting with appendix syndrome the one and acute left iliac fossa pain the other.…”
Section: Discussionmentioning
confidence: 97%
“…Normal adnexal torsion is rare during pregnancy. Çılgın H et al indicated 6 that plasma heat shock protein 70 level could be used as a serum marker in the early detection of adnexal torsion since its significant increase in the study group was 1.50fold and 1.47-fold respectively (P = 0.001) than that in the laparotomy and control groups, following 12 h of adnexal torsion. Ayachi A et al reported 7 two cases of adnexal torsion during the second trimester of pregnancy; presenting with appendix syndrome the one and acute left iliac fossa pain the other.…”
Section: Discussionmentioning
confidence: 97%
“…Several studies have shown that some serum biomarkers, such as serum d-dimer, IL-6, IL-8, tumor necrosis factor-alpha (TNF-α), heat shock protein 70, and ischemia-modified albumin, can play a role in the early detection of OT [ 7 27 28 29 ]. Kart et al [ 29 ] studied the diagnostic value of plasma d-dimer levels in an experimental rat OT model and found a significant correlation between plasma d-dimer levels and the histopathological damage scores of ovarian injuries.…”
Section: Discussionmentioning
confidence: 99%
“…Kart et al [ 29 ] studied the diagnostic value of plasma d-dimer levels in an experimental rat OT model and found a significant correlation between plasma d-dimer levels and the histopathological damage scores of ovarian injuries. Cilgin et al [ 28 ] investigated the role of serum heat shock protein 70 in a rat model and suggested that levels of this protein seemed to be a useful serum marker for the early detection of OT. Aran et al [ 7 ] showed that serum ischemia-modified albumin levels were correlated with the histological scores of the specimens in an experimental rat OT model.…”
Section: Discussionmentioning
confidence: 99%